2013
DOI: 10.1186/1477-7819-11-240
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis and systematic review: adjuvant interferon therapy for patients with viral hepatitis-related hepatocellular carcinoma

Abstract: ObjectiveTo evaluate the efficacy and safety of adjuvant IFN therapy for viral hepatitis-related hepatocellular carcinoma (HCC) after treatment with surgical resection or transarterial chemoembolization (TACE).MethodsControlled trials of adjuvant treatment with IFN for patients with HCC published between 2000 and 2012 were searched electronically in MEDLINE, PubMed, Cochrane Library, and EMBASE databases. According to the heterogeneity of the studies, two different models - the fixed-effect model and the rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…A Japanese group previously showed positive effects of acyclic retinoids and vitamin K analogues on recurrence-free survival, but overall survival was not improved and large-scale studies were not performed appropriately [128,129] . Interferon has been suggested as an adjuvant therapy after resection [130] . According to a large current database in Taiwan, antiviral therapies reduce the recurrence of HCC after surgery in patients with chronic hepatitis B or C [131,132] .…”
Section: Adjuvant Therapy After Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Japanese group previously showed positive effects of acyclic retinoids and vitamin K analogues on recurrence-free survival, but overall survival was not improved and large-scale studies were not performed appropriately [128,129] . Interferon has been suggested as an adjuvant therapy after resection [130] . According to a large current database in Taiwan, antiviral therapies reduce the recurrence of HCC after surgery in patients with chronic hepatitis B or C [131,132] .…”
Section: Adjuvant Therapy After Resectionmentioning
confidence: 99%
“…In agreement, a randomized controlled trial conducted in China showed better recurrence-free survival (RR = 0.651, 95%CI: 0.451-0.938) and overall survival (RR = 0.420, 95%CI: 0.271-0.651) in patients receiving antiviral therapy, especially in terms of prevention of late recurrence [133] . It would be reasonable to recommend nucleoside or nucleotide analogues or interferon therapy to patients with hepatitis B and pegylated interferonbased therapy to patients with hepatitis C after curative hepatic resection [130][131][132][133] .…”
Section: Adjuvant Therapy After Resectionmentioning
confidence: 99%
“…Therefore, it might be possible that tumors will develop in the future even after HCV elimination when only a DAA regimen is used. Much like the reports demonstrating that IFN treatment has the ability to suppress the growth of hepatocellular carcinoma,45, 46 our new finding that RBV has the ability to suppress lipogenesis in hepatic cells will shed light once again on the beneficial abilities of RBV not only for antiviral but also antipathogenic treatments of liver diseases, such as hepatic steatosis or hepatocellular carcinoma, in which aberrant lipogenesis is involved.…”
Section: Discussionmentioning
confidence: 67%
“…Several studies have demonstrated the suppressive effect of IFN-α in the development of HCC in patients with chronic hepatitis [45][46][47][48]. Thus IFN-α therapy for hepatitis B (HBV) and C (HCV) viral infections suppresses carcinogenesis and improves liver function [49][50][51][52].…”
Section: Ifns In Clinical Oncologymentioning
confidence: 99%